Inversor multiníveis quasi-Z-source com fonte CC única e compartilhamento de potência ativa entre os módulos - Guisso, Ronaldo Antonio (2019)
Due to its ability to provide Maximum Power Point Tracking (MPPT) control and independent regulation of the DC bus voltage, this makes the inverter quasi-Z-Source (qZS) an attractive candidate for applications in photovoltaic (PV) systems. To improve the quality of the waveform of the current injected into the grid, cascaded multilevel inverters has gained great interest. In order to understand these concepts, the qZS Cascaded Multilevel Inverter (qZS-CMI) based grid-tie PV systems has previously been proposed. Compared with other inverters, the named Single DC Source quasi-Z-Source Cascade Multilevel Inverter (SS qZS-CMI) has the ability to make use of a single DC source to share active power for all cascaded qZS modules. This is accomplished by replacing its Z-impedance inductances by coupled inductors. The qZS-CMI provides the distributed MPPT, and keeps the DC bus voltage regulation producing a true symmetric CMI topology. In spite of this, a set with strings of separate PV panels are required, making it suitable for PV systems with a few dozens of kilo-Watts (kW) or more. Aiming to keep the advantages of the qZS-CMI for smaller PV systems, this work proposes a novel topology, SS qZS-CMI. Thus providing a detailed analysis of the operation with a design methodology for the hardware, as well as the modeling and controller design. Experimental results are provided to prove the operation of the proposed system and the control strategy implemented. Keywords: cascade loop controller, cascade multilevel inverter (CMI), DC-AC converter, electrical engineering, LCL filter, power electronics, quasi-Z-source inverter (qZSI), renewable energy sources.